Pengaruh Kepuasan Kerja, Motivasi Kerja, Dan Perilaku Karyawan Terhadap Kinerja Dan Disiplin Sebagai Variabel Moderator di PT. Vetco Gray Indonesia - Nurhandika Sepvia Putri; Ramli; Sajiyo (Program Studi Manajemen FEBM UMRAH, 2025)
Creating good employee performance is not an easy task because, in reality, there are still employees who frequently encounter issues related to discipline and attendance at work. Considering the significant role and position of human resources in the Company’s business activities, a high level of work discipline is required. This study aims to examine the influence of job satisfaction, work motivation, and employee behavior on performance and discipline. The research method used is multiple linear regression analysis with a population of 170 employees and a sample of 119 employees. The results of the study show that the job satisfaction variable, when moderated by discipline, has a significant effect on performance. The work motivation variable, when moderated by discipline, also has a significant effect on performance. Furthermore, the employee behavior variable, after being moderated by discipline, demonstrates a significant influence on performance